2020
DOI: 10.1002/ctm2.161
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the murine gut microbiome impacts humoral immunity induced by rabies vaccines

Abstract: Background Gut microbiome plays a crucial role in modulating human and animal immune responses. Rabies is a fatal zoonosis causing encephalitis in mammals and vaccination is the most effective method to control and eliminate rabies. The relationship between the gut microbiome and humoral immunity post rabies vaccination has not been investigated yet. Methods Mice orally administrated with a cocktail of broad‐spectrum antibiotics were inoculated with rabies vaccines, and humoral immune response was analyzed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Vancomycin also demonstrated consistent vaccine-modulatory effects of subsequent studies wherein: (i) vancomycin, but not ampicillin, robustly impacted alum-adjuvant OVA vaccine-specific titers in a different mouse strain (C57Bl/6; Figure S3A); (ii) vancomycin decreased antigenspecific IgG titers and T cell responses when mice were vaccinated with OVA adjuvanted with a novel lipid nanoparticle (LNP)-based adjuvant (Figure S4A-D); and (iii) vancomycin reduced antigen-specific IgG titers against a clinically relevant hepatitis B vaccine conducted in two geographically distinct vivaria (Figure S4E-F). Vancomycin treatment has previously been shown to disrupt response to nonadjuvanted inactivated influenza vaccine [22] and rabies vaccine [54], and is included in many antibiotic cocktails used to perturb the microbiome for vaccination studies with variable effects on individual vaccine antigens [22,26,28,54]. Vancomycin treatment has also been shown to modulate several immune-related pathways [55][56][57][58], and reduces the abundance of bacteria belonging to Clostridiales and Bacteroidales, while allowing increases in Proteobacteria [55][56][57][58][59], in agreement with our data (Figure 1C).…”
Section: Vancomycin-induced Vaccine Hyporesponse Is Minimized By Allowing Sufficient Time For the Microbiome To Recovermentioning
confidence: 99%
“…Vancomycin also demonstrated consistent vaccine-modulatory effects of subsequent studies wherein: (i) vancomycin, but not ampicillin, robustly impacted alum-adjuvant OVA vaccine-specific titers in a different mouse strain (C57Bl/6; Figure S3A); (ii) vancomycin decreased antigenspecific IgG titers and T cell responses when mice were vaccinated with OVA adjuvanted with a novel lipid nanoparticle (LNP)-based adjuvant (Figure S4A-D); and (iii) vancomycin reduced antigen-specific IgG titers against a clinically relevant hepatitis B vaccine conducted in two geographically distinct vivaria (Figure S4E-F). Vancomycin treatment has previously been shown to disrupt response to nonadjuvanted inactivated influenza vaccine [22] and rabies vaccine [54], and is included in many antibiotic cocktails used to perturb the microbiome for vaccination studies with variable effects on individual vaccine antigens [22,26,28,54]. Vancomycin treatment has also been shown to modulate several immune-related pathways [55][56][57][58], and reduces the abundance of bacteria belonging to Clostridiales and Bacteroidales, while allowing increases in Proteobacteria [55][56][57][58][59], in agreement with our data (Figure 1C).…”
Section: Vancomycin-induced Vaccine Hyporesponse Is Minimized By Allowing Sufficient Time For the Microbiome To Recovermentioning
confidence: 99%
“…Since the 1960s, germ-free mouse, chicken, and pig models have demonstrated that the microbiome influences vaccine response ( 119 – 124 ). More recently, microbiota disruption via antibiotic treatment in mice has corroborated these early observations ( 125 127 , 130 , 131 , 133 ). Multiple antibiotics from different classes and with different breadths of activity have been shown to decrease vaccine response ( Table 3 ).…”
Section: Linking the Microbiome And Response To Vaccinesmentioning
confidence: 55%
“…The PCR reactions were conducted using the following program: denaturation at 95 °C for 3 min, 27 cycles of 95 °C for 30 s, annealing at 55 °C for 30 s, elongation at 72 °C for 45 s, and a final extension at 72 °C for 10 min. The PCR components, the extraction and purification of PCR products were the same with previous study [ 29 ]. Purified PCR products were pooled into equimolar amounts and sequenced on the Illumina MiSeq platform according to the standard protocols by Shanghai Majorbio Bio-pharm Technology Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%